Double Entry Diaries: A Strategy for Teaching Reading Comprehension - Vivin K Modjanggo (Sintuwu Maroso Journal of English Teaching, 2016)
The objective of this research is to know the effect of double entry diaries strategy toward students’ reading comprehension. The sample of this research was Class XI IPA 3 consisted of 28 students. This research was pre-experimental research design. Based on the result of the study, it indicates that the use of double entry diaries strategy can affect students’ achievement in reading comprehension.Keywords: double entry diaries, strategy, reading comprehension.